A systematic review and meta-analysis on endovascular treatment as an attractive alternative for acute superior mesenteric venous thrombosis. (April 2022) - Wang, Lixin; Wang, Enci; Liu, Fei; Zhang, Wei; Shu, Xiaolong; Guo, Daqiao; Fu, Weiguo
Objective: This systematic review and meta-analysis evaluated the published data on the efficacy and safety of therapies for superior mesenteric venous thrombosis (SMVT), aiming to provide a reference and set of recommendations for clinical treatment. Methods: Relevant databases were searched for studies published from 2000 to June 2020 on SMVT treated with conservative treatment, surgical treatment, or endovascular approach. Different treatment types were grouped for analysis and comparison, and odds ratios with corresponding 95% confidence intervals were calculated. The outcomes were pooled using meta-analytic methods and presented by forest plots. Results: Eighteen articles, including eight on SMVT patients treated with endovascular therapies, were enrolled. The treatment effectiveness was compared between different groups according to the change of symptoms, the occurrence of complications, and mortality as well. The conservative treatment group had better efficacy compared to the surgery group (89.0% vs. 78.6%, P <0.05), and the one-year survival rate was also higher (94.4% vs. 80.0%, P > 0.05), but without statistical significance. As for endovascular treatment, the effectiveness was significantly higher than the surgery group (94.8% vs. 75.2%, P <0.05), and the conservative treatment group as well (93.3% vs. 86.3%, P > 0.05), which still requires further research for the lack of statistical significance. Conclusions: Present findings indicate that anticoagulation, as conservative treatment should be the preferred clinical option in the clinic for SMVT, due to its better curative effect compared to other treatment options, including lower mortality, fewer complications, and better prognosis. Moreover, endovascular treatment is a feasible and promising approach that is worth in-depth research, for it is less invasive than surgery and has relatively better effectiveness, thus can provide an alternative option for SMVT treatment and may be considered as a reliable method in clinical.